A novel therapeutic paradigm for patients with extensive alopecia areata. (2nd August 2016) - Renert-Yuval, Yael; Guttman-Yassky, Emma
ABSTRACT: Introduction : Alopecia areata (AA) is a common, T-cell mediated, hair-centered skin disease that lacks efficacious, long-term therapies for extensive disease. Systemic immune suppressants are usually used, despite their nonspecific actions, often associated with substantial side effects. Although, the Th1 pathway was suggested as pivotal in the disease, recent studies suggest that Th2, Th9, phosphodiesterase (PDE) 4, and IL-23 axes might contribute to AA pathogenesis. Areas covered : This paper provides an overview of activated immune pathways in AA and possible therapeutic modalities. Expert opinion : The translational revolution leading to improved therapeutic strategies has just begun for AA. These treatments are often associated with better safety and higher efficacy compared to currently used immune-suppressants. Different pathways might drive the inflammatory process in AA. Ongoing and future clinical trials utilizing narrow- targeted therapeutics will be able to better elucidate the role of each cytokine pathway in creating the AA disease phenotype.